2019
DOI: 10.3390/biom9120861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Iso-Mukaadial Acetate and Ursolic Acid Acetate as Plasmodium falciparum Hypoxanthine-Guanine-Xanthine Phosphoribosyltransferase Inhibitors

Abstract: To date, Plasmodium falciparum is one of the most lethal strains of the malaria parasite. P. falciparum lacks the required enzymes to create its own purines via the de novo pathway, thereby making Plasmodium falciparum hypoxanthine-guanine-xanthine phosphoribosyltransferase (PfHGXPT) a crucial enzyme in the malaria life cycle. Recently, studies have described iso-mukaadial acetate and ursolic acid acetate as promising antimalarials. However, the mode of action is still unknown, thus, the current study sought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The results showed that carbocyclic acid and hydroxyl were the main functional groups responsible to bond with the significant amino acid residues on each receptor, while hydrocarbon emerges as the potential component that can be modified in future drug development due to its unintended interaction with the amino acid residues. After doing a literature review about the effects of UA compounds on various targets from various diseases, we found that hydroxyl and carboxyl groups play a crucial role in the interaction of amino acids at the receptors; hence, we are in the same conclusions [7,23,24].…”
Section: A 2b 2c 2d Fig 2: A-d 2d Visualization Of Pharmacophore Mode...mentioning
confidence: 56%
See 1 more Smart Citation
“…The results showed that carbocyclic acid and hydroxyl were the main functional groups responsible to bond with the significant amino acid residues on each receptor, while hydrocarbon emerges as the potential component that can be modified in future drug development due to its unintended interaction with the amino acid residues. After doing a literature review about the effects of UA compounds on various targets from various diseases, we found that hydroxyl and carboxyl groups play a crucial role in the interaction of amino acids at the receptors; hence, we are in the same conclusions [7,23,24].…”
Section: A 2b 2c 2d Fig 2: A-d 2d Visualization Of Pharmacophore Mode...mentioning
confidence: 56%
“…The UA acetate had strong binding affinities for the PfHGXPT and the dissociation constant (KD) reaching 2.8396 µM as reported in the study. The precise contacts and high affinities found in the binding pockets of human and PfHGXPT were demonstrated using molecular docking and dynamics simulations [7].…”
Section: Introductionmentioning
confidence: 99%
“…Radicals such as hydroxyl radicals have the potential to damage DNA, lipids and proteins. 14,[33][34][35] Results on Figure 3 proved that exposing pET30 plasmid DNA to Fenton's reagent caused complete damage of plasmid DNA. This is due to hydroxyl radical since it reacts with nitrogen bases of DNA causing production of both base radicals and sugar radicals which then react and results in breakage of sugar phosphate leading to DNA damage.…”
Section: Resultsmentioning
confidence: 92%
“…19,20 The spread of multi-drug resistance in malaria treatment and the absence of new antimalarial compounds requires an urgent need for new drug regime for malaria, which kills 11 million people every year. [19][20][21][22] There is a growing interest in drug combinations as an alternative new treatment approach against malarial parasite. Azithromycin is a macrolide antibiotic that is particularly attractive as an antimalarial because of its safety in children.…”
Section: Multi-target Drugs In Malariamentioning
confidence: 99%